Model Kewirausahaan Sosial Di Pondok Pesantren Miftahul Hikmah Sukorejo Parengan Tuban - Dian Rosita Hariyati; Agus Wahyu Irawan; Shelvyna Rikantasari (Akademika, 2022)
Entrepreneurship model whose business is partly for social and partly for business development. The problem raised is how the social entrepreneurship model at Miftahul Hikmah Islamic Boarding School Sukorejo Parengan Tuban, the research method used is a qualitative research method, namely by describing the results of the study. The results of the research on the social entrepreneurship model at Miftahul Hikmah Islamic Boarding School cover three points, namely, the entrepreneurship education model in the form of training and field practice. Ma'arif Mart's cooperative social entrepreneurship model, namely, students as employees, Part of the results of kopontren's business for pesantren, as well as the HCG (Hikma Collection Group) social entrepreneurship model, namely students as employees and some of the proceeds are used for pesantren. The social entrepreneurship model is in accordance with the four elements of social entrepreneurship, namely, the existence of social values, economic activities, innovation and civil society.